THE USE OF VOCAL VIBRATIONS TO IMPROVE ENGLISH PRONUNCIATION FOR DHH LEARNERS - Mahardhika, Adyuta; Sulistyani, Ummi Nur Laila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teaching English pronunciation to Deaf and Hard of Hearing (DHH) students remains challenging, especially given limited access to auditory input and the need to adapt teaching methods to students’ conditions. Although previous studies have highlighted the importance of multisensory approaches, there is still a limited explanation of how tactile techniques, such as vocal vibration, are used in real classroom situations. This study aims to explore the challenges teachers face, the strategies they use, and how the vocal vibration technique is implemented in teaching pronunciation. This research used a descriptive qualitative design and was conducted in a senior high school in Pekalongan, involving one class of 20 DHH students. The data were collected through classroom observations and teacher interviews and analyzed through thematic analysis, including coding, categorization, and interpretation. The results show that students have difficulties in perceiving sounds, monitoring their own pronunciation, and controlling their articulation. To address these challenges, teachers use repetition, multisensory strategies, and tactile techniques. The vocal vibration technique helps students improve their awareness of how sounds are produced, their pronunciation accuracy, and their class participation. However, the results vary depending on each student’s hearing level. Therefore, flexible and adaptive teaching approaches are needed to support pronunciation learning for DHH students.